2007
DOI: 10.1302/0301-620x.89b10.19038
|View full text |Cite
|
Sign up to set email alerts
|

Does bone quality predict loosening of cemented total hip replacements?

Abstract: We matched 78 patients with a loose cemented Charnley Elite Plus total hip replacement (THR) by age, gender, race, prosthesis and time from surgery with 49 patients with a well-fixed stable hip replacement, to determine if poor bone quality predisposes to loosening. Clinical, radiological, biomechanical and bone mineral density indicators of bone quality were assessed. Patients with loose replacements had more pain, were more likely to have presented with atrophic arthritis and to have a history of fragility f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 35 publications
0
45
1
4
Order By: Relevance
“…Conversely, there are multiple studies that have shown no association between patient obesity (BMI C 30 kg/m 2 ) and aseptic loosening rates [13,27,36,39,57]. Although our study was unable to analyze other host factors, previous studies have associated younger age [4,6,15,21,24,36,41,45,53], increased activity level [11,16,44,52], and tobacco use [20] with increased rates of aseptic loosening. To appropriately analyze whether these host factors have an association with aseptic loosening, future studies should report their raw data regarding the incidence of aseptic loosening with each of these various factors.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Conversely, there are multiple studies that have shown no association between patient obesity (BMI C 30 kg/m 2 ) and aseptic loosening rates [13,27,36,39,57]. Although our study was unable to analyze other host factors, previous studies have associated younger age [4,6,15,21,24,36,41,45,53], increased activity level [11,16,44,52], and tobacco use [20] with increased rates of aseptic loosening. To appropriately analyze whether these host factors have an association with aseptic loosening, future studies should report their raw data regarding the incidence of aseptic loosening with each of these various factors.…”
Section: Discussionmentioning
confidence: 54%
“…Among modifiable risk factors, multiple factors such as high activity level [3,14,17,30,43,44,48], obesity [2,9,10,34,37,38,43,46,48,51,52], and smoking [10,12,16,17,19,32,35,41] may be associated with an increase in the risk of aseptic loosening after THA.…”
Section: Discussionmentioning
confidence: 99%
“…69 Aside from radiographic imaging studies that seek to qualify and quantify the presence of aseptic loosening via image analysis, other viable avenues have emerged that may prove of some benefit when attempting to evaluate the progression of debrisinduced bone resorption such as dual-energy X-ray absorptiometry (DEXA), morphometric grid analysis of lytic lesion advancement, and radiographic texture analysis (RTA) of trabecular bone patterns. [70][71][72][73] Furthermore, adequate biologic markers of osteolysis must be identified to evaluate the condition's progression to supplement where imaging evaluation has fallen short. One such possibility is the use of peripheral blood levels of CD14 þ CD16 þ monocytes which have proven to be sensitive markers of aseptic loosening.…”
Section: Future Directions Imaging Modalitiesmentioning
confidence: 99%
“…Osteoporosis and osteoarthritis are not mutually exclusive conditions, and many patients undergoing hip replacement also have unrecognized osteoporosis or deficiency of vitamin D (2). Osteoporosis have 3 major potential complications in total hip arthroplasty (THA): perioperative fracture, an increased risk of periprosthetic fracture (Figure 1), and a risk of late aseptic loosening ( Figure 2) due to mechanical failure of ingrown trabecular bone (3,4). Osteoarthritis is one of the most common joint disorder.…”
Section: Introductionmentioning
confidence: 99%